Immunohistochemical detection of IgM and IgG in lung tissue of dogs with leptospiral pulmonary haemorrhage syndrome (LPHS). (June 2015) - Schuller, Simone; Callanan, John J.; Worrall, Sheila; Francey, Thierry; Schweighauser, Ariane; Kohn, Barbara; Klopfleisch, Robert; Posthaus, Horst; Nally, Jarlath E.
Highlights: Leptospiral pulmonary haemorrhage syndrome (LPHS) is a severe form of leptospirosis. LPHS is associated with high mortality in both humans and animals. Deposition of IgG and IgM is present in the majority of canine LPHS lung tissues. No leptospiral antigens were detectable in canine LPHS lung. Findings suggest that autoimmunity may be involved in the pathogenesis of LPHS. Abstract: Leptospiral pulmonary haemorrhage syndrome (LPHS) is a severe form of leptospirosis. Pathogenic mechanisms are poorly understood. Lung tissues from 26 dogs with LPHS, 5 dogs with pulmonary haemorrhage due to other causes and 6 healthy lungs were labelled for IgG ( n  = 26), IgM ( n  = 25) and leptospiral antigens ( n  = 26). Three general staining patterns for IgG/IgM were observed in lungs of dogs with LPHS with most tissues showing more than one staining pattern: (1) alveolar septal wall staining, (2) staining favouring alveolar surfaces and (3) staining of intra-alveolar fluid. Healthy control lung showed no staining, whereas haemorrhagic lung from dogs not infected with Leptospira showed staining of intra-alveolar fluid and occasionally alveolar septa. Leptospiral antigens were not detected. We conclude that deposition of IgG/IgM is demonstrable in the majority of canine lungs with naturally occurring LPHS, similar to what has been described in other species. Our findings suggest involvement of the host humoral immunity in the pathogenesis of LPHS and provide further evidence to support the dog as a natural disease model for human LPHS.